Ontologi Hibualamo dalam Perspektif Jurgen Habermas - Nanuru, Ricardo Freedom (Jurnal Filsafat "WISDOM", 2011)
Hibua Lamo is a cultural system that binds communities in North Halmahera. It is a form of conflict resolution among the communities by harmonizing interests between conflicting groups as well as binding the groups into a new relationship bond. It was tested by riots of Moluccas, including North Halmahera. This study shows that there is a difference context of emergence between Habermas's thought and local knowledge of Hibua Lamo. However, based on the Habermas's perspective of communication ratio, Hibua Lamo at least get the spirit to a new birth. Based on the new understanding, Hibua Lamo now exists to rely on communicative ratio which is able to withstand annexation of market system and the state, and also to tie the communities in North Halmahera through peace consensus.Keywords: Hibua Lamo, Jürgen Habermas, local knowledge, communicative ratio.